An overview of angiogenesis inhibitors in Phase II studies for non-small-cell lung cancer. (September 2015) - Pilotto, Sara; Novello, Silvia; Peretti, Umberto; Kinspergher, Stefania; Ciuffreda, Ludovica; Milella, Michele; Carbognin, Luisa; Vavalà, Tiziana; Ferrara, Roberto; Caccese, Mario; Tortora, Giampaolo; Bria, Emilio
<x xml:space="preserve">Abstract</x> Introduction: Angiogenesis plays a major role in the development and progression of solid tumors, including lung cancer. Although some anti-angiogenic agents have demonstrated a statistically significant advantage in terms of primary outcome in clinical trials, the reliable clinical benefit obtained with these drugs is still questionable and often quantitatively limited. To better clarify this complex scenario and definitively establish the concrete benefits of anti-angiogenic strategies in lung cancer, several clinical trials have been conducted with others currently ongoing. Areas covered: In this review, the authors highlight the data ascertained from Phase II trials conducted in NSCLC patients who are treated with recently discovered innovative anti-angiogenic molecules. The authors also discuss older widely investigated anti-angiogenic drugs that have been repurposed or used in different contexts and combinations. Expert opinion: Globally considered, the results of the countless clinical trials evaluating anti-angiogenic agents suggest that angiogenesis (with its molecules and pathways) represents a non-ideal druggable process for several biologically relevant reasons. Consequently, it is important that the conceptual development and clinical validation of anti-angiogenic agents is different from those employed for traditional target agents (i.e., erlotinib, gefitinib and crizotinib). Indeed, the development and validation of these agents still represents a major challenge for modern scientific research.